CONCEPTUAL BASIS OF TRAINING OF MATHEMATICS TEACHERS - Bozorov Zokir Yuldosh o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The content and essence of training future mathematics teachers in educational organizations, the content and essence of training students, and the importance of the elementary mathematics course in the training of future mathematics teachers are highlighted.